Female Gaming, Gaming Addiction, and the Role of Women Within Gaming Culture: A Narrative Literature Review - Lopez-Fernandez, Olatz; Williams, A. Jess; Griffiths, Mark D.; Kuss, Daria J. (Frontiers in Psychiatry, 2019)
Research investigating female gaming has begun to emerge despite gaming being traditionally more popular with males. Research in the 21st century has drawn attention to the role of women in culture, society, and technology, and female gaming is one of the growing phenomena not to have been researched in-depth. The aim of the present paper was to review female gaming (i.e., the role of females within video game culture), and identify any associated psychopathological symptomatology. The review adapted the Sample, Phenomenon of Interest, Design, Evaluation, Research (SPIDER) model in conducting a narrative literature review. A search of three scientific electronic databases yielded 49 papers for further evaluation. From a methodological perspective, studies had to fulfil the following criteria to be included: (i) published between the years 2000-2018; (ii) assessed female gaming or the female position within gaming culture, (iii) contained quantitative, qualitative, or mixed methods approaches to produce empirical data or discussing theoretical implications through reviews, (iv) be retrievable as full-text peer-reviewed journal paper, and (v) published in English, German, Polish, Spanish, Italian, Portuguese or French. Four categories emerged from the papers: (i) the benefits of female gaming, (ii) why women might play videogames less than men, (iii) perceptions and realities of female characters within videogames, and (iv) women’s position in gaming culture. The main findings showed playing videogames has benefits for women in terms of enhancing cognitive, social, and physical abilities. However, they are less encouraged to play videogames due to negative expectations based on gender and/or experiences during game play. Videogames are associated with stereotypical male characteristics, such as being overly aggressive, and frequently contain sexualised content. Female gamers appear to require coping strategies to handle online harassment. Females look for different things in videogames, which are not often included in game designs thereby limiting their abilities. For instance, female avatar representation – which is exaggerated and hyper-sexualised – can prompt social comparisons and lead to feelings of decreased self-esteem, depression, and other impacts on wellbeing. Overall, there are still obstacles for women playing videogames even though they comprise half of the gaming population.